Faster response to water level increase facilitates Salix cavaleriei survival in Lake Erhai. Issue 1 (1st January 2019) - Wu, Ai-Ping; Zhao, Ya-Xuan; Qi, Liang-Yu; Zhu, Guo-Rong; Chen, Fa-Lin; Liang, Yun-Shan; Cao, Te; Zhong, Wen
Abstract: The roles that adventitious roots play in flooding tolerance have been well-studied in willows, while which of the maximum height of adventitious roots and the abundance of adventitious roots in willows is more important for their flooding tolerance is not well known. In this study, we analyzed the effects of adventitious roots on the flooding tolerance of Salix cavaleriei by comparing the maximum height of adventitious roots and the abundance of adventitious roots in dead and live willows along a flooding gradient from 0 to 180 cm in Lake Erhai, China. The results showed that willow mortality increased drastically when the water depth suffered by willows exceeded 100 cm. Live willows developed more adventitious roots and produced them higher on the trees compared with dead willows, however, the pest infestation percentage of the dead willows was larger. Additionally, both the maximum height and the abundance of adventitious roots in live willows were significantly correlated with water depth, whereas in dead willows, these variables were not significantly correlated or only weakly correlated with water depth. The results indicate that producing adventitious roots higher on the trees may be more important than developing abundant adventitious roots lower on the trees when S. cavaleriei is subjected to high flooding levels. Our data highlight that a faster adventitious root response promotes this species' survival under flood stress, although pest infestation accounts for a small percentage of willow mortality. Accordingly, we should choose those willows that can develop more abundant adventitious roots and higher on the stems to plant in regions with abrupt water-level fluctuations.